Mechanical, Team‐Focused, Video‐Reviewed Cardiopulmonary Resuscitation Improves Return of Spontaneous Circulation After Emergency Department Implementation. Issue 6 (17th March 2020) - Rolston, Daniel M.; Li, Timmy; Owens, Casey; Haddad, Ghania; Palmieri, Timothy J.; Blinder, Veronika; Wolff, Jennifer L.; Cassara, Michael; Zhou, Qiuping; Becker, Lance B.
Abstract : Background: Outcomes in cardiac arrest remain suboptimal. Mechanical cardiopulmonary resuscitation (CPR) has not demonstrated clear clinical benefit; however, video review provides the capability to monitor CPR quality and provide constructive feedback to individuals and teams to improve their performance. The aim of our study was to evaluate cardiac arrest outcomes before and after initiation of a mechanical, team‐focused, video‐reviewed CPR intervention. Methods and Results: In 2018, our emergency department began using mechanical CPR; a new team‐focused strategy with nurse‐led Advanced Cardiovascular Life Support; and biweekly, multidisciplinary video review of cardiac arrests. A revised approach to resuscitation was generated from a performance improvement session, and in situ simulation was used to disseminate our approach. The primary outcome of this study was the return of spontaneous circulation rate before and after our mechanical, team‐focused, video‐reviewed CPR intervention. Secondary outcomes included survival to admission and discharge. Multivariable logistic regression modeling was used. The pre‐ and postintervention groups were similar at baseline. A total of 248 patients were included in our study (97 before and 151 after mechanical, team‐focused, video‐reviewed CPR). Return of spontaneous circulation was higher in the intervention group (41% versus 26%; P =0.014). There were nonsignificant increases in survival to admission (26% versus 20%; P =0.257) and survival to discharge (7% versus 3%; P =0.163). After controlling for covariates, the odds of return of spontaneous circulation remained higher after the intervention (odds ratio, 2.11; 95% CI, 1.14–3.89). Conclusions: Implementation of our mechanical, team‐focused, video‐reviewed CPR intervention for cardiac arrest patients in our emergency department improved return of spontaneous circulation rates. Survival to hospital admission and discharge did not improve.